SCALE DEVELOPMENT AND VALIDATION TO MEASURE STUDENT’S BEHAVIORAL INTENTION TO VOTE - Mohamad Rosman, Mohamad Rahimi; Zulkifli, Nursyahida; Wan Mohamad Noor, Wan Nurul Basirah; Johari, Nor Farizah; Hassan, Muhammad Syafiq; Hussin, Siti Nor Adawiah (Journal of Islamic, Social, Economics and Development, 2024)
Voting behavior is essential to support the democratic system since the people have the same opportunity to vote in the election. That is why political education should be started earlier, especially for the youth, so that they know the importance of participating in the election by casting a vote. However, it is reported that the turnout rate among youth is considered low. Before the 14th General Election (GE14), young Malaysian voters aged 21 to 30 outnumbered senior voters by 2 to 1. Therefore, this study aims to establish a measurement scale of young voters' behavioral intention to vote. Relevant literature on intention to vote among youth was reviewed, and responses from 422 students of Universiti Teknologi MARA, Malaysia, aged 18 to 29 years. The responses were collected through an online questionnaire to explore the factor structure and validate the scale. Confirmatory factor analysis (CFA) using SmartPLS (version 3.3.3) was used to validate the scale. In conclusion, the study's findings recommend the extension of the scale development and validation used for future studies. It will facilitate and provide valuable perspectives for various parties, such as political parties, to consider this a winning factor in future elections.